An Approximate Solution for a Second Order Elliptic Inverse Coefficient Problem with Nonlocal Integral - Hussein, M. S.; A.Qahtan, Jehan; E. Dyhoum, Taysir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This article studies the nonlocal inverse boundary value problem for a rectangular domain, a second-order, elliptic equation and a two-dimensional equation. The main objective of the article is to find the unidentified coefficient and provide a solution to the problem. The two-dimensional second-order, convection equation is solved directly using the finite difference method (FDM). However, the inverse problem was successfully solved the MATLAB subroutine lsqnonlin from the optimization toolbox after reformulating it as a nonlinear regularized least-square optimization problem with a simple bound on the unknown quantity. Considering that the problem under study is often ill-posed and that even a small error in the input data can have a large impact on the outcome, Tikhonov’s regularization technique is used to obtain stable and regularized results.